Hospitality and tourism demand : exploring industry shifts, themes, and trends - Sampaio, Carlos (2024)
Tourism demand is critical for the hospitality industry and is influenced by a set of continuously changing factors. The tourism and hospitality industries play a critical role in many regions and countries, supporting the local economy, providing employment, and fostering economic and social development with effects across multiple industries. This study aims to analyse the nature of tourism and hotel demand through a thematic analysis. By conducting a review of the existing literature published over the period of 2018–2023, this research identifies overarching patterns, trends, and themes characterising the current research landscape. Research results reveal significant insights into market trends and strategic industry shifts. It particularly emphasises areas such as customer demand forecasting, technology integration, and sustainability, which are crucial for understanding demand fluctuations. The findings offer insights into the theoretical foundations of tourism and hotel demand and provide practical implications for industry stakeholders aiming to strategise effectively in a dynamic market.